Halal Restaurant: What Makes Muslim In Kuching Confident? - Fahdlina, Aleefah; Jamal Abdul, Nassir Shaari; Muhammad, Khalique (Journal of Economic Development, Management, IT, Finance and Marketing, 2014)
This paper is an outcome of a research project investigating on the scenario surrounding Halal restaurants in major cities and tourism destinations in Malaysia. It investigates factors that influence Muslim confidence level in choosing Halal restaurant to dine in and/or purchase food for their friends or relatives. From researchers exhaustive reviews on existing literature related to Halal concepts and extensive fieldwork studies, four variables were proposed, namely Devoutness; Awareness; and Lifestyle; tested for their influence on Confidence Level. For this paper, the report is on 250 questionnaires analyzed from 265 distributed at 10 restaurants deemed to be the most popular and mostly visited around Kuching City, the capital and main city for State of Sarawak in East Malaysia. The results show that all variables are significantly correlated, while regression analyses approved the hypotheses proposing the independent variables as factors that influence the confidence level of consumers in selecting halal restaurant.